Design of E-Commerce Payment System at Tokopedia Online Shopping Site - MN, Achmad Zainuddin; Junaidi, Junaidi; Putra, Renaldy Dwi (Pandawan, 2017)
Developments in information technology very rapidly in recent years a positive impact on many aspects of life, including in the business world. One concept that is assessed that the new business is E-Commerce or Commonly called Online Business. There are many sites that do Transactions of Goods or Services through E-Commerce, for example, the Sale and Purchase at online shopping sites in Tokopedia which emphasizes the Transaction Customer to Customer (C2C). C2C is one model of e-commerce in this case consumers sell directly to consumers who want to buy, or may be called as a transaction between the consumer. Activity C2C can be done in many ways over the internet. Auksi is one example of the best known C2C activities. Many people make purchases and sales on eBay and hundreds of auction website. Other examples of C2C activities are classification advertising, personal services, exchange, sale of virtual properties and supporting services. In the online shopping site that emphasizes C2C Transactions Transactions Using Transactions Rekber piggybank so as to secure for consumers. Rekber piggybank principle similar to that occurred in Escrow Payment System, the system Rekber piggybank an agreement between the seller and the buyer or producer and the consumer to use the services of a third person as the place of payment and the payee. Therefore Rekber piggybank exists to support and secure the sale and purchase of Online Transactions on the site piggybank. So that the transaction using the system Rekber piggybank can be used as a system that can promise Consumers and sellers can trust each other.